Comparison of Quality of Porous Structure Specimens Produced by Different Additive Technologies and from Different Materials - Jozef Tkac; Teodor Toth; Ondrej Mizera; Vieroslav Molnar; Gabriel Fedorko; Miroslav Dovica (Applied Sciences, 2024)
Lattice and gyroid structures are often subjected to additive technologies to produce various types of products, and the current market has a number of 3D printers that can be used for their production. The quality of the products produced in this way can be assessed on the basis of technical parameters and the filament used. Such an approach, however, is insufficient. In terms of quality, other product parameters need to be assessed, such as the surface texture and the internal structure’s porosity. For such an assessment, we can use the industrial tomography method and the method of roughness measurement via an optical microscope. The paper presents research on the assessment of the surface texture and porosity in lattice and gyroid structures. For the research, two types of test specimens—a specimen with a lattice structure and a specimen with a gyroid structure—were prepared. The obtained results proved that the 3D printing technology directly impacted the surface texture and porosity. For experimental specimens produced by SLS technology, we found that it was very important to carefully remove the excess powder, as unremoved powder can significantly affect the porosity results. For specimens produced by FDM technology, the research confirmed that some “gaps” between the layers were not pores but defects created during specimen production. When analyzing the surface using the Alicon Infinite G5 optical microscope, we found that the measured roughness results were directly impacted by the specimen’s surface color, the structure’s geometry, and the ambient light, which was confirmed by a red lattice experimental specimen, the surface of which could not be scanned. Based on the above, it can be stated that the selection of 3D technology for additive production needs must be given adequate attention regarding the quality of the created structures and textures.